Palyno‐morphological characteristics of gymnosperm flora of pakistan and its taxonomic implications with LM and SEM methods. Issue 1 (17th October 2017) - Khan, Raees; Ul Abidin, Sheikh Zain; Ahmad, Mushtaq; Zafar, Muhammad; Liu, Jie; Amina, Hafiza
Abstract: The present study is intended to assess gymnosperms pollen flora of Pakistan using Light Microscope (LM) and Scanning Electron Microscopy (SEM) for its taxonomic significance in identification of gymnosperms. Pollens of 35 gymnosperm species (12 genera and five families) were collected from its various distributional sites of gymnosperms in Pakistan. LM and SEM were used to investigate different palyno‐morphological characteristics. Five pollen types (i.e., Inaperturate, Monolete, Monoporate, Vesiculate‐bisaccate and Polyplicate) were observed. Six In equatorial view seven types of pollens were observed, in which ten species were sub‐angular, nine species were Traingular, six species were Perprolate, three species were Rhomboidal, three species were semi‐angular, two species were rectangular and two species were prolate. While five types of pollen were observed in polar view, in which ten species were Spheroidal, nine species were Angular, eight were Interlobate, six species were Circular, two species were Elliptic. Eighteen species has rugulate and 17 species has faveolate ornamentation. Eighteen species has verrucate and 17 have gemmate type sculpturing. The data was analysed through cluster analysis. The study showed that these palyno‐morphological features have significance value in classification and identification of gymnosperms. Based on these different palyno‐morphological features, a taxonomic key was proposed for the accurate and fast identifications of gymnosperms from Pakistan. Abstract : For the first time SEM and LM palyno‐morphological features was used to identify gymnosperm flora of Pakistan. Using these palyno‐morphological features a taxonomic key was prepared for fast, accurate and as an aid identification of gymnosperms. SEM and LM palyno‐morphological features were found significant for the identification of gymnosperm species.